Pressurized groundwater outflow experiments and numerical modeling for outflow channels on Mars. Issue 12 (23rd December 2014) - Marra, Wouter A.; Hauber, Ernst; McLelland, Stuart J.; Murphy, Brendan J.; Parsons, Daniel R.; Conway, Susan J.; Roda, Manuel; Govers, Rob; Kleinhans, Maarten G.
Abstract The landscape of Mars shows incised channels that often appear abruptly in the landscape, suggesting a groundwater source. However, groundwater outflow processes are unable to explain the reconstructed peak discharges of the largest outflow channels based on their morphology. Therefore, there is a disconnect between groundwater outflow processes and the resulting morphology. Using a combined approach with experiments and numerical modeling, we examine outflow processes that result from pressurized groundwater. We use a large sandbox flume, where we apply a range of groundwater pressures at the base of a layer of sediment. Our experiments show that different pressures result in distinct outflow processes and resulting morphologies. Low groundwater pressure results in seepage, forming a shallow surface lake and a channel when the lake overflows. At intermediate groundwater pressures, fissures form and groundwater flows out more rapidly. At even higher pressures, the groundwater initially collects in a subsurface reservoir that grows due to flexural deformation of the surface. When this reservoir collapses, a large volume of water is released to the surface. We numerically model the ability of these processes to produce floods on Mars and compare the results to discharge estimates based on previous morphological studies. We show that groundwater seepage and fissure outflow are insufficient to explain the formation of large outflow channels from a single event. Instead, formation of a flexure‐induced subsurface reservoir and subsequent collapse generates large floods that can explain the observed morphologies of the largest outflow channels on Mars and their source areas.